Pengaruh yogurt sinbiotik pisang terhadap kadar glukosa dan insulin tikus sindrom metabolik - Fiqhi Cahyaningrum Rahmawati; Kis Djamiatun; Nyoman Suci (Minat S2 Gizi dan Kesehatan, Prodi S2 IKM, FK-KMK UGM, 2017)
Background: The metabolic syndrome often begins with insulin resistance characterized by hyperinsulinemia and hyperglycemia. Synbiotic yoghurt tanduk banana contains probiotic and prebiotic FOS can improve insulin resistance in metabolic syndrome.Objective: To prove the effect of synbiotic yoghurt tanduk banana can reduce blood glucose levels and insulin levels in metabolic syndrome rats.Method: True-experimental study with randomized controlled group pre-post test design in male wistar rats. Eighteen samples were induced to become metabolic syndrome with high fat fructose diet for 2 weeks and they were divided into 3 groups: control (K) was given standard diet, treatment group 1 (P1), and treatment group 2 (P2) were given sinbiotic yoghurt tanduk banana dose of 0.009 ml/g body weight (BW)/day and 0.018 ml/g BW/day for 2 weeks.Results: The paired t-test showed there were differences of blood glucose levels and insulin levels before and after treatment in P2 group. The Kruskal Wallis test showed there were differences of mean blood glucose levels inter group after treatment (p<0.05). The One-way Anova test showed there were differences of mean insulin levels inter group after treatment (p<0.05). Conclusion: Synbiotic yoghurt tanduk banana can reduce blood glucose levels and insulin levels in metabolic syndrome rat with effective dose is 0.018 ml/grBW/day.